Post-accord monetary developments in the United States - KAREKEN, J.H. (PSL Quarterly Review, 2014)
As the official System position at the time of the Accord, the “new theory of credit control” served as a justification for the Federal Reserve’s desire to abandon once-and-for-all the wartime pattern of rigidity pegged interest rates. Now that sufficient time has passed and the Federal Reserve has moved to a more traditional defence of the classical techniques of monetary control, a detailed examination of the theory’s influence on monetary policy is warranted. The present work argues that the legacy of the war years, i.e. a large national debt, remains as an obstacle to the effective working of such a policy. A brief summary of the new theory of credit control and its central thesis that the Federal Reserve could, using classical techniques, successfully fulfil its traditional function without creating instability in the market for government securities is provided. The post accord experience and the significance of developments in this period are then reviewed in detail. The author concludes that the significance of the existence of a large public debt lies in the fact that it has facilitated the expansion of the effective money supply and has served to reduce whatever effectiveness classical monetary policy had, since the traditional techniques cannot deal with attempts at a more intensive utilisation of a given nominal money supply. For this reason, the very existence of a large public debt suggests the need for a far greater reliance on direct methods of monetary control. JEL: E51, E52, E58